2015
DOI: 10.5137/1019-5149.jtn.15773-15.0
|View full text |Cite
|
Sign up to set email alerts
|

The management of intracranial aneurysms during pregnancy: a systematic review

Abstract: It has been estimated that 1.8% of women of childbearing age (16 to 44 years) develop intracranial aneurysms, however the incidence of unruptured intracranial aneurysms during pregnancy is not well established in the literature (25). Rupture of intracranial aneurysms occurs in the range of 1 to 10 per 100,000 pregnancies (1, 33). Case fatality from subarachnoid hemorrhage during pregnancy is reported as high as 83%, but outcomes have improved with better medical care (10, 12). Cerebrovascular management of ane… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
26
0
7

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(35 citation statements)
references
References 46 publications
2
26
0
7
Order By: Relevance
“…It can also be dangerous for the baby because of radiations during the procedure if delivery has not yet been performed. 3 Diagnosis of aneurysm rupture was suspected during delivery for our patient, which allowed the obstetrician to extract the child and begin studies to underpin the diagnosis. It is true that the baby is on the safe side if delivery occurs before aneurysm treatment because of anesthesia risk, maternal hemodynamic variations due to aneurysm rupture such as vasospasm and hypoxia, dehydration, and acidosis due to low uterine perfusion.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…It can also be dangerous for the baby because of radiations during the procedure if delivery has not yet been performed. 3 Diagnosis of aneurysm rupture was suspected during delivery for our patient, which allowed the obstetrician to extract the child and begin studies to underpin the diagnosis. It is true that the baby is on the safe side if delivery occurs before aneurysm treatment because of anesthesia risk, maternal hemodynamic variations due to aneurysm rupture such as vasospasm and hypoxia, dehydration, and acidosis due to low uterine perfusion.…”
Section: Discussionmentioning
confidence: 94%
“…The differential diagnosis is eclampsia crisis which can delay proper care. 2 In their literature review, Barbarite et al 3 reported that endovascular approach was mostly compared with clipping, respectively 47.7% against 36.4%. Endovascular treatment is harmless and allows a short hospitalization, but can be dangerous because of the heparin therapy that follows if a cesarian section is planned after.…”
Section: Discussionmentioning
confidence: 99%
“…36 In a recent systematic review on the management of intracranial aneurysms in pregnant women, the authors showed that coil embolization was performed more often than surgical clipping, probably due to the less invasive nature of coiling and shorter operating times. 38 However, coil embolization during pregnancy exposes the developing fetus to potential radiation-related risks. These risks depend on the dose and the stage of pregnancy at the time of radiation, varying from death of the embryo (embryogenesis during the first 2 weeks) to congenital abnormalities (organogenesis during week 2 to 7) to growth retardation and childhood cancer (fetal period from week 8 until birth).…”
Section: Intracranial Aneurysmsmentioning
confidence: 99%
“…Por otro lado, la incidencia de HSA se incrementa durante la gestación, y su frecuencia aumenta con la edad de la madre y la paridad (1). Una revisión de la literatura sobre hemorragia intracraneal en el embrazo indica que la HSA representa el 34,8 % de los eventos hemorrágicos intracraneales durante el embarazo, y que de estos, el 26,7 % tienen desenlaces fatales para la madre (6), mientras que se reporta una mortalidad entre 7 a 25 % para el feto (7,8).…”
Section: Introductionunclassified
“…Los cambios hemodinámicos normales asociados al embarazo podrían generar estrés vascular importante, e incrementarían el riesgo en la formación de aneurismas, su progresión y consecuente ruptura (7). En el embarazo se evidencian aumentos del 50 al 60 % en el gasto cardiaco, volumen plasmático, hipercoagulabilidad y cambios del sistema endócrino (9, 10).…”
Section: Introductionunclassified